Effect of temperature on the microstructure and mechanical properties of TiC/Fe matrix composites fabricated by spark plasma sintering - Chuan Wang; Yong Li; Wanpeng Zhang; Tianwen Zhao; Huiqiao Du (Journal of Materials Research and Technology)
The effects of sintering temperatures on the microstructures and mechanical properties of titanium carbide particles reinforced iron matrix composites (TiC/Fe MCs) fabricated by the spark plasma sintering (SPS) process with pure element powders have been systematically investigated. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), electron back scattering diffractometer (EBSD), and energy dispersive spectroscopy (EDS) have been conducted for microstructural analysis. The results show that with increasing sintering temperatures, the porosity of the composites initially decreases and then increases. Simultaneously, the grain size gradually diminishes while element diffusion becomes more uniform. Upon reaching a critical sintering temperature (1120 °C), the original grain size disappears and carbides undergo decomposition and reprecipitation to reach an equilibrium state, with which optimal comprehensive properties can be achieved (porosity decreases to a minimum of 3.85%, grain size of 2.69 μm, Vickers hardness reaches 595 HV0.5, bending strength is at 662 MPa, coefficient of friction is at 0.74, and wear loss to 0.21 mg). These property enhancements have been attributed to reduced porosity in the composites, decreased grain size, and improved anchoring effect of carbides within the matrix. Additionally, the primary fracture mechanisms and wear mechanisms of TiC/Fe MCs with different process parameters have been analyzed. When the temperature is below 1080 °C, intergranular fracture predominates, whereas transgranular and ductile fractures become predominant above this threshold. When the temperature is below 1120 °C, fatigue wear, oxidation wear, and abrasive wear are predominantly observed. Conversely, when the temperature exceeds 1120 °C, oxidation wear and abrasive wear become the primary mechanisms.